Event Management Analysis of the Java International Vape Expo 2024 in Creating a Connecting Space for Indonesian Vapers - Salsadilla, Gadisha; Frisiska, Frisiska; Heykal, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Humans are cultural creatures. Each region, tribe, language and group can have a different culture. Culture is influenced by the surrounding environment. Habits that are continuously carried out together will become a popular culture that is easily spread like vaping. Vaping is an innovation in technology and is a transformation from conventional cigarettes to electronic cigarettes. Throughout its journey, vaping has experienced many changes, starting from regulations, form, type, to function. Some people use vape because of necessity, and some people use vape because of their lifestyle. This lifestyle is based on the word